Methanol decomposition on the β-Ga 2 O 3 (1 0 0) surface: A DFT approach - Branda, Maria Marta (2007)
Density functional theory (DFT) cluster model calculations on methanol reactions on the β-Ga 2 O 3 (1 0 0) surface have been realized. β-Ga 2 O 3 structure has tetrahedral and octahedral ions and the results of gallia-methanol interaction are different depending on the local surface chemical composition. The surface without oxygen vacancies is very reactive and produces the methanol molecule decomposition. The unsaturated surface oxygen atoms strongly oxidize the methanol molecule. CO 2 and H 2 O molecules are produced when methanol reacts with a free oxygen vacancy surface on octahedral gallium sites. On the other hand, H 2 CO is found after the reaction of this molecule with a free O vacancy surface on tetrahedral gallium sites. A weak interaction between the remaining CO 2 molecule and the oxide surface was found, being this molecule easy to desorb. Otherwise, H 2 CO has a stronger surface bond and it could suffer a later oxidation. © 2007 Elsevier B.V. All rights reserved.